T-type Calcium Channels in Basic and Clinical Science - Schaffer, Stephen W.; Li, Ming (Springer Vienna : Imprint: Springer, 2015)
T-type calcium channels are prevalent in every organ of the body, and are believed to play a part in a variety of physiological processes, including contraction, shape change, secretion, endo- and exocytosis, cell proliferation and differentiation, modulation of enzyme function, and cell cycle progression. As such, research on the roles of these channels in a wide range of diseases has attracted increasing attention in recent years. The purpose of this book is to present a series of unique and comprehensive reviews of our current understanding of T-type calcium channels at the level of the basic sciences as well as the clinical sciences. For key organ systems, information is provided on the correlation between the molecular, biophysical and pharmacological properties of the channels, their cellular mechanisms, and their potential roles in the pathogenesis of various diseases. The compilation presents both commonplace and less well-known findings on these channels in a format designed to appeal to both casual readers and specialists in basic and clinical research on these transporters.